A Commensal Streptococcus Dysregulates the Pseudomonas aeruginosa Nitrosative Stress Response - Baty, Joshua J.; Huffines, Joshua T.; Stoner, Sara N.; Scoffield, Jessica A. (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic infections in the cystic fibrosis (CF) airway are composed of both pathogenic and commensal bacteria. However, chronic Pseudomonas aeruginosa infections are the leading cause of lung deterioration in individuals with CF. Interestingly, oral commensals can translocate to the CF lung and their presence is associated with improved lung function, presumably due to their ability to antagonize P. aeruginosa. We have previously shown that one commensal, Streptococcus parasanguinis, produces hydrogen peroxide that reacts with nitrite to generate reactive nitrogen intermediates (RNI) which inhibit P. aeruginosa growth. In this study, we sought to understand the global impact of commensal-mediated RNI on the P. aeruginosa transcriptome. RNA sequencing analysis revealed that S. parasanguinis¬ and nitrite-mediated RNI dysregulated expression of denitrification genes in a CF isolate of P. aeruginosa compared to when this isolate was only exposed to S. parasanguinis. Further, loss of a nitric oxide reductase subunit (norB) rendered an acute P. aeruginosa isolate more susceptible to S. parasanguinis-mediated RNI. Additionally, S. parasanguinis¬-mediated RNI inactivated P. aeruginosa aconitase activity. Lastly, we report that P. aeruginosa isolates recovered from CF individuals are uniquely hypersensitive to S. parasanguinis¬-mediated RNI compared to acute infection or environmental P. aeruginosa isolates. These findings illustrate that S. parasanguinis hinders the ability of P. aeruginosa to respond to RNI, which potentially prevents P. aeruginosa CF isolates from resisting commensal and host-induced RNI in the CF airway.